3D N-heterocyclic covalent organic frameworks for urea photosynthesis from NH3 and CO2 - Ning Li; Jiale Zhang; Xiangdong Xie; Kang Wang; Dongdong Qi; Jiang Liu; Ya-Qian Lan; Jianzhuang Jiang (Nature Communications)
Abstract Artificial photosynthesis of urea from NH3 and CO2 seems to remain still essentially unexplored. Herein, three isomorphic three-dimensional covalent organic frameworks with twofold interpenetrated ffc topology are functionalized by benzene, pyrazine, and tetrazine active moieties, respectively. A series of experiment results disclose the gradually enhanced conductivity, light-harvesting capacity, photogenerated carrier separation efficiency, and co-adsorption capacity towards NH3 and CO2 in the order of benzene-, pyrazine-, and tetrazine-containing framework. This in turn endows tetrazine-containing framework with superior photocatalytic activity towards urea production from NH3 and CO2 with the yield of 523 μmol g−1 h−1, 40 and 4 times higher than that for benzene- and pyrazine-containing framework, respectively, indicating the heterocyclic N microenvironment-dependent catalytic performance for these three photocatalysts. This is further confirmed by in-situ spectroscopic characterization and density functional theory calculations. This work lays a way towards sustainable photosynthesis of urea.